Personnel Policy Strategy of the National Police of Ukraine in the Context of Updating Administrative and Legal Principles of Protecting Human Rights and Freedoms - A. V. Tanko (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article presents the results of the legal and scientific researches analysis of the personnel policy strategy of the National Police of Ukraine in the context of updating administrative and legal principles of protecting human rights and freedoms.